ISLAMIZATION OF SCIENCE (EPISTEMOLOGICAL-HISTORICAL STUDIES) - Afifi, Zaki (Jurnal Ilmiah Pesantren, 2023)
The discussion about the dichotomy between science and religion is still not over. Epistemological and historical aspects are very important in forming the concept of scientific integration in order to end the problem of scientific dichotomy. This is a literature research that explores the problem of scientific dichotomy and the concept of Islamization of science epistemologically and historically as one of the concepts of scientific integration. The data in this research are thoughts and the data was collected from the literature of previous scholars and researchers. Analysis is carried out using context analysis. This research reveals that the problem of scientific dichotomy is caused by westernization of science. The idea of Islamization of Science is a solution to this problem because it means returning science to its nature (integrative and godly). It is hoped that this research will provide scientific insight for scholars and a philosophical basis for educational institutions in carrying out the educational process.